Seismic Reflection, Distribution, and Potential Trap of Permian Volcanic Rocks in the Tahe Field - 蒲仁海 张云龙 罗静兰 (Journal of earth science (Wuhan, China), 2012)
Permian Kaipaileicike （开派雷兹克） volcanic rocks approximately 0-200 m thick are drilled in the Tahe （塔河） field. The distribution of volcanic rocks and their potential to form hydrocarbon reservoirs are discussed based on the integrated interpretation of log and 3D seismic data. The volcanic rocks, mainly consisting of dacites and basalts, are sandwiched between the Lower Triassic and Lower Carboniferous and bounded by top and bottom unconformities. The dacites accumulated in a mound shape around volcanic craters, whereas the basalts are deposited in tabular or trough-fill ge- ometries. Permian volcanic craters mainly located at the northwest corner of the Tahe field are identi- fied from volcanic rock thickening, occurrence of volcanic breccias, structural arch of the top Permian, seismic attribute anomalies, and fault （piercing conduit） reflections. Along the northwest wing of a Carboniferous salt dome, a stratigraphic trap is formed by a northeast updip pinch-out of Permian volcanic rock. Oil indications within the trap are found in numerous wells. The reservoir volcanic rocks are mainly of the fracture-pore pattern and covered by the caprock of a Lower Triassic mudstone. The hydrocarbon reservoir, which can potentially be a medium-sized oil pool, is connected to Camhrian-Ordovician source rocks through normal faults along the salt dome boundary.